A Collaborative Project to Bridging the Gap between Basic and Clinical Teachers: The Opinion of Medical Students. (28th May 2015) - Sentí, Mariano; Miralles, Ramon; Bigorra, Joan; Girvent, Meritxell; Minguella, Joan; Samsó, Enric; Solsona, José-F.; Baños, Josep-E.
Abstract : The organization of medical curricula with a clear distinction between basic and clinical subjects makes it difficult for teachers to collaborate and teach students in an integrated way. We designed a new subject, Integrated Medicine, to overcome such limitations. Here, we describe the evaluation of the first three years of running the experience, as well as the opinion of the first group of students in their sixth year. Three cohorts of first-year medical students( n = 158 ) and eight teachers, as well as a group of students of sixth year( n = 41 ), participated in the experiment. Students worked following the problem-based learning approach. Their satisfaction, their subjective improvement of content knowledge in basic and clinical fields, and their belief about the accomplishment of educational objectives were evaluated. The results showed a high level of satisfaction, increased content knowledge, and improvement in solving problems, searching for relevant information, team working, and oral and written communication skills. Students of sixth year agreed that the subject helped them to better understand the clinical manifestations of disease, the diagnosis process, and therapeutic approaches. In conclusion, experiences such as Integrated Medicine may enhance the integration of knowledge by the joint work of basic and clinical teachers.